Psychometric Properties of the Icelandic Version of the M5-50 and its Relationship to Age, Education, Gender, Political Affiliation, and Salary. - Franz Jónas Arnar Arnarson 1993- (2018)
This goal of this study was to 1) assess the psychometric properties of an Icelandic translation of the M5-50 questionnaire, which is used to measure personality according to the five-factor model of personality, 2) to assess gender difference in personality factors as measured by the M5-50, and 3) to assess relationship between personality factors and political affiliation. Participants answered the M5-50 and demographic questionnaires on the website prof.egummig.is. The sample included 540 participants, 302 women and 238 men, between the age of 18 to 78. The results suggest that the Icelandic translation of the M-50 has a five-factor structure, with each of the factors showing acceptable or good reliability, with room for improvement regarding few of the items on the questionnaire. As suggested by evolutionary theories on personality, gender difference in personality were observed suggesting that despite efforts to increase gender equality in Iceland, personality profiles of men and women remain different. Indicating that as levels of human development increase so do gender differences in personality. Relationships between personality factors and political affiliation were also observed indicating that participants that voted for the Pirate Party differed the most compared to other participants on extraversion and conscientiousness. Keywords: personality, five-factor model, gender difference, political affiliation. Markmið rannsóknarinnar var að 1) meta próffræðilega eiginleika íslenskrar þýðingar á M5-50 persónuleikaprófinu sem er ætlað að mæla persónuleika út frá fimm þátta líkaninu um persónuleika, 2) að meta kynjamun á persónuleikaþáttaeinkennum út frá M5-50, og 3) að meta tengsl milli persónuleikaþáttaeinkenna og stjórnmálaskoðana. Þátttakendur svöruðu prófinu ásamt lýðfræðilegum spurningum á vefsíðunni próf.égummig.is. Úrtak rannsóknarinnar voru 540 þátttakendur, 302 konur og 238 karlar, á aldrinum 18 til 18 ára. Niðurstöðurnar benda til þess að íslensk þýðing M5-50 mælir fimm þætti, með ásættanlegan ...